2016
DOI: 10.1186/s12889-016-3311-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of complications of diabetes mellitus among patients visiting the diabetes clinic at Sampa Government Hospital, Ghana: a descriptive study

Abstract: BackgroundDiabetes mellitus (DM) appears to be a global epidemic and an increasingly major non-communicable disease threatening both affluent and non-affluent society. The study aimed to determine the knowledge of diabetic complications among diabetes mellitus clients visiting the Diabetic Clinical at Sampa Government Hospital, Ghana.MethodThis questionnaire-based descriptive study recruited a total 630 patients visiting the Diabetes Clinic at the Sampa Government Hospital. Structured questionnaire was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
75
6
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 22 publications
17
75
6
5
Order By: Relevance
“…However, these findings are inconsistent with the findings of Obirikoranget al conducted among the patients visiting the diabetes clinic at the Sampa Government Hospital of Ghana [16].…”
Section: Resultscontrasting
confidence: 89%
“…However, these findings are inconsistent with the findings of Obirikoranget al conducted among the patients visiting the diabetes clinic at the Sampa Government Hospital of Ghana [16].…”
Section: Resultscontrasting
confidence: 89%
“…In our study, the majority of respondents knew about a diabetic foot as a complication of diabetes mellitus and stroke as a complication of hypertension. A study by Obirikorang et al conducted in Ghana showed that type 2 diabetes mellitus complication commonly known by diabetic patients was a diabetic foot (51.5 %) [21], which was consistent with our study findings. Knowledge scores in our study showed that the majority of respondents did not know about diabetes mellitus complications and the majority had inadequate knowledge about hypertension complications.…”
Section: Discussionsupporting
confidence: 93%
“…Knowledge scores in our study showed that the majority of respondents did not know about diabetes mellitus complications and the majority had inadequate knowledge about hypertension complications. Our study findings were consistent with a study by Obirikorang et al conducted in Ghana indicating that a higher proportion of type 2 diabetes patients did not have adequate knowledge on diabetic complications [21]. A study by Adepu et al showed that at baseline the majority of participants were unaware of asymptomatic hypertension and complications associated with it [22].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Pretested structured interviewer-administered questionnaire, which is adapted from different literatures, was used to collect the data (15,(23)(24)(25)(26). The questioner contains 28 diabetes complications related awareness items.…”
Section: Data Collection Instrument and Proceduresmentioning
confidence: 99%